Digital marketing in Icelandic travel agencies : main digital media channels used - Guðbjörg Una Hallgrímsdóttir 1991- (2021)
The tremendous growth of information and communication technology (ICT), particularly the Internet and advances in information search, has led to a significant transformation and unprecedented opportunities for the tourism industry. The travel industry has grown to be the most common category of products and services sold on the Internet, and the Internet plays a significant role in marketing and selling tourism products. The changed landscape of the industry has therefore called for a new emphasis on the marketing activities of tourism companies, making digital marketing one of the influential future trends of the tourism industry. This research is intended to aid in explaining the concept of digital marketing and to analyze the role of digital marketing in the tourism industry today. The main objective is to provide insight into the practice of digital marketing among Icelandic travel agencies and how they use the main digital media channels for marketing purposes. The thesis explores both the theoretical aspects of the subject as well as the results of qualitative and quantitative research based on in-depth interviews on the one hand and an online survey and website evaluation on the other. The results show that most Icelandic travel agencies seem to understand the value of digital marketing and they are becoming more aware of how beneficial it can be for tourism companies. The results also showed that the most used and valued digital media channels were websites, social media marketing, SEO, and mobile marketing. However, the findings also suggest that many websites lack fundamental elements that should be present on a website. This research contributes new knowledge and a better understanding to digital marketing for tourism companies in Iceland, especially travel agencies. Furthermore, the result will benefit travel agencies in Iceland, by helping them understand where they stand in terms of digital marketing and how they can use digital marketing to improve their overall marketing and business performance ...